Hippo-YAP/TAZ pathway regulation: the crucial roles of lncRNAs in cancer - Wonyi Jang; Mijung Im; Jungwook Roh; JiHoon Kang; Wanyeon Kim (Animal Cells and Systems, 2023)
ABSTRACTThe Hippo signaling pathway is a conserved signaling pathway that regulates cell proliferation, apoptosis, and differentiation and plays essential roles in the maintenance of organ size and tissue homeostasis. Also, this signaling pathway is a critical regulator of malignant progression in a wide range of cancers. Furthermore, it has been established that YAP and TAZ are major effectors of the Hippo signaling pathway and transcription co-activators that regulate the expressions of genes involved in cell growth and differentiation. Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides involved in several biological processes, including chromatin remodeling, transcriptional regulation, and post-transcriptional processing. Evidence suggests that the aberrant expression and dysregulation of lncRNAs contribute to the development and progression of various malignancies by acting as oncogenes or tumor suppressors. In addition, many studies have shown that lncRNAs can directly or indirectly regulate the Hippo-YAP/TAZ signaling pathway in cancer. Here, we overview the roles played by lncRNAs in tumor progression with focus on their regulation of the Hippo-YAP/TAZ signaling pathway and discuss their potential usages as clinical biomarkers and therapeutic targets.